Coupled Climate Responses to Recent Australian Wildfire and COVID‐19 Emissions Anomalies Estimated in CESM2. Issue 15 (2nd August 2021) - Fasullo, J. T.; Rosenbloom, N.; Buchholz, R. R.; Danabasoglu, G.; Lawrence, D. M.; Lamarque, J.‐F.
Abstract: Multiple 50‐member ensemble simulations with the Community Earth System Model version 2 are performed to estimate the coupled climate responses to the 2019–2020 Australian wildfires and COVID‐19 pandemic policies. The climate response to the pandemic is found to be weak generally, with global‐mean net top‐of‐atmosphere radiative anomalies of +0.23 ± 0.14 W m −2 driving a gradual global warming of 0.05 ± 0.04 K by the end of 2022. While regional anomalies are detectable in aerosol burdens and clear‐sky radiation, few significant anomalies exist in other fields due to internal variability. In contrast, the simulated response to Australian wildfires is a strong and rapid cooling, peaking globally at − 0.95 ± 0.15 W m −2 in late 2019 with a global cooling of 0.06 ± 0.04 K by mid‐2020. Transport of fire aerosols throughout the Southern Hemisphere increases albedo and drives a strong interhemispheric radiative contrast, with simulated responses that are consistent generally with those to a Southern Hemisphere volcanic eruption. Plain Language Summary: Significant perturbations in aerosol and other climate forcing emissions accompanied both the 2019–2020 Australian wildfires and the COVID‐19 pandemic‐induced changes in human activity. This analysis estimates the coupled climate response to each event in 50‐member simulation ensembles using the Community Earth System Model version 2. The simulations depict a modest climate warming that evolves gradually through 2022 driven by COVID‐19 pandemic responses with a timing and initial magnitude consistent with recent meteorological studies. In contrast, a strong and abrupt climate cooling resulting from Australian wildfire emissions is simulated, with global‐scale responses arising in part from contrasts in radiation anomalies between hemispheres. Responses to wildfires include a northward displacement of tropical deep convection, similar to what is seen after major extratropical volcanic eruptions, suggesting the potential for an influence on the El Niño/Southern Oscillation. Key Points: The response to COVID‐19 in CESM2 is modest, amounting globally to a peak 0.23 ± W m −2 heating and 0.05 ± 0.04 K warming through 2022 In contrast, the Australian wildfires cool the globe by 0.95 ± 0.15 W m −2 in December 2019 and 0.06 ± 0.04 K by mid‐2020 Significant water cycle responses are driven by Australian wildfires, including a northward displacement of tropical deep convection